Application of Electre Method Decision Support System for Laptop Selection - Ani Yoraeni Hasan (Komunitas Dosen Indonesia, 2023)
In the contemporary era, laptops have transitioned from being perceived as luxury items to becoming an essential tool for work, education, and various learning activities. The market is saturated with a plethora of laptop manufacturers, providing consumers with a wide array of options to cater to their specific needs and budget constraints. However, a common challenge faced by consumers is the mismatch between their requirements and the specifications of available laptops, often due to a lack of understanding. Addressing this issue requires the implementation of a suitable Decision Support System (DSS). The proposed solution involves employing the Electre method, renowned for its multicriteria approach. This method systematically eliminates unsuitable alternatives, facilitating the identification of laptops that align with the desired criteria. The process involves several key steps, such as defining criteria and alternatives, assigning weights, normalizing the decision matrix, determining concordance and discordance indices, and ultimately establishing an aggregate dominance matrix. By leveraging the Electre method, this Decision Support System can effectively recommend laptops that not only meet the consumer's specified criteria but also align with their budget constraints. This systematic approach aims to enhance the overall decision-making process, ensuring optimal satisfaction for laptop buyers in terms of both performance and financial considerations.